2012
DOI: 10.4315/0362-028x.jfp-12-192
|View full text |Cite
|
Sign up to set email alerts
|

First Detection and Seasonal Variation of Lipophilic Toxins Okadaic Acid, Dinophysistoxin-1, and Yessotoxin in Korean Gastropods

Abstract: Okadaic acid (OA), dinophysistoxin-1 (DTX1), pectenotoxin-2, and yessotoxin (YTX) are classes of lipophilic toxins found in marine animals. OA and DTX1 accumulation causes diarrhetic shellfish poisoning, a worldwide public health problem. Diarrhetic shellfish poisoning has not previously been reported in gastropods, which are widely consumed in Korea. Seasonal variation in marine lipophilic toxins in gastropods was investigated using liquid chromatography-tandem mass spectrometry. Eighty specimens of Neptunea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…The above data indicated that the amount of OA and DTX-1 accumulated in digestive glands was more than four times greater than that in flesh. This result was similar to the reported paper (Lee et al 2012). …”
Section: Contamination Of Commercially Available Seafoodsupporting
confidence: 94%
“…The above data indicated that the amount of OA and DTX-1 accumulated in digestive glands was more than four times greater than that in flesh. This result was similar to the reported paper (Lee et al 2012). …”
Section: Contamination Of Commercially Available Seafoodsupporting
confidence: 94%
“…Currently, gold nanoparticles have been applied in various biosensors and immunochromatographic strips to detect small molecular toxins. , One emerging immunoassay for mycotoxins and phycotoxins is a immunochromatographic strip that uses conjugate antibody-colored gold nanoparticle as a signal reagent. ,, The principle of immunochromatographic strip depends on the migration of test samples and gold nanoparticle–antibody conjugates along membrane strips on which the binding interactions occur. Because the results of the strip can be inspected visually, the strip provides simple and fast on-site detection in less than 10 min without proficient personnel or other equipment. ,, Since various levels of OA contamination have been reported in shellfish samples collected from different regions, an effective method for on-site detecting OA in shellfishes is required. Therefore, this study produced a mAb against OA and successfully applied it to an ultrasensitive ELISA and gold nanoparticle immunochromatographic strip for detecting OA in shellfish samples.…”
Section: Introductionmentioning
confidence: 99%
“…The lead compound of the group, yessotoxin (YTX), was first isolated in 1986 from the digestive glands of scallop P. yessoensis collected in Mutsu Bay (Japan), from which the toxin acquired its name [ 216 ]. Thereafter, YTXs have been detected worldwide, in shellfish from Korea [ 217 ], Chile, and New Zealand. In Europe, they have been described in mollusks from Norway, Italy, Spain, and Russia [ 212 ].…”
Section: Unknown Receptors: Yessotoxinsmentioning
confidence: 99%